Impaired kidney function is associated with intraplaque hemorrhage in patients undergoing carotid endarterectomy. (November 2017) - Wesseling, Marian; van Koeverden, Ian D.; van Lammeren, Guus W.; van der Laan, Sander W.; Haitjema, Saskia; de Vries, Jean-Paul P.M.; den Ruijter, Hester M.; de Jager, Saskia C.A.; Hoefer, Imo; Blankestijn, Peter; Verhaar, Marianne; de Kleijn, Dominique P.V.; et al.
Abstract: Background and aims: Previously, we showed that patients undergoing carotid endarterectomy have an increased risk for major atherosclerotic events in the presence of moderate or poor kidney function. Acceleration of vascular inflammatory responses is considered to be causally involved in progression of atherogenesis and poor outcome in chronic kidney disease patients. The association between kidney function and plaque composition has not been thoroughly investigated yet. The aim of this study was to investigate the association between kidney function and atherosclerotic plaque composition in patients undergoing carotid endarterectomy. Methods: Atherosclerotic plaques, harvested from 1796 patients who underwent carotid endarterectomy, were immunohistochemically stained for macrophages, smooth muscle cells, calcifications, collagen, microvessels, lipid core size and intraplaque hemorrhage. Cytokines were measured in plaque and plasma and associated with kidney function. Quantitative proteomics were performed on 40 carotid plaques and associated with kidney function. Results: Decreased kidney function was associated with increased odds ratio of intraplaque hemorrhage, OR 1.15 (95% CI; 1.02–1.29 ( p  = 0.024)) and increased odds ratio of fibrous-atheromatous plaques (plaques with lipid core presenting more than 10% of total plaque surface) OR 1.21 (95% CI; 1.07–1.38 ( p  = 0.003)) per decrease of 20 points in eGFR. Proteomics revealed that decreased kidney function was associated with upregulation of the classical pathway of the complement system and the intrinsic pathway of the coagulation system. Conclusions: Decreased kidney function was associated with plaque hemorrhage but not with inflammatory plaque characteristics. Our data suggests that other pathways than the inflammation-pathway are involved in plaque vulnerability and poor outcome in patients with decreased kidney function. Highlights: The first large atherosclerotic plaque study reporting on associations between kidney function and plaque composition. Higher prevalence of fibrous-atheromatous lesions and intraplaque hemorrhage in patients with decreased kidney function. In patients undergoing carotid endarterectomy, impaired kidney function associated with poor outcome during follow up. The inflammation-pathway is not involved in plaque vulnerability and poor outcome in patients with decreased kidney function.